Oncologic outcomes in patients with nonurothelial bladder cancer. - Patel, Sanjay G.; Weiner, Adam Benjamin; Keegan, Kirk; Morgan, Todd (Indian Journal of Urology)
Introduction: We aimed to evaluate the relative prognostic impact of the most common variant histologies on disease‑specific survival (DSS) in patients undergoing radical cystectomy. Materials and Methods: The Surveillance, Epidemiology, and End Result database was used to identify patients who underwent radical cystectomy for bladder cancer from 1990 to 2007. Patients with urothelial cell carcinoma (UCC), squamous cell carcinoma (SCC), adenocarcinoma (AC), sarcoma, small cell carcinoma, signet ring carcinoma, and spindle cell carcinoma were included in the study. Multivariable analysis was performed using Cox proportional hazards model to assess independent predictors of disease-specific survival (DSS). Mortality rates were estimated using Kaplan–Meier analyses. Results: A total of 14,130 patients met inclusion criteria with the following histologies: UCC (90.1%), SCC (4.6%), AC, (2.3%), sarcoma (0.8%), small cell carcinoma (0.8%), signet ring carcinoma (0.5%), and spindle cell carcinoma (0.9%). Three‑year DSS was most favorable in patients with UCC (63.7%; 95% confidence interval [62.9%–64.8%]) and AC (65.3% [59.3%–70.6%]), whereas 3-year DSS was the least favorable for small cell carcinoma (41.6% [31.3%–51.6%]) and sarcoma (45.4% [35.1%–55.1%]). In the multivariable analysis, independent predictors of DSS were age, marital status, grade, T‑stage, N‑stage, and variant histology. With respect to UCC, there was an increased risk of disease‑specific death associated with all variants except AC. Sarcoma and spindle cell carcinoma were associated with the highest risk of death. Conclusions: With the exception of AC, the most common variant bladder cancer histologies are all independently associated with worse DSS relative to UCC in patients undergoing radical cystectomy.